Assessment of iron bioavailability and protein quality of new fortified blended foods in broiler chickens - Fiorentino, Nicole Marie (Kansas State University, 2017)
Fortified-blended foods (FBFs), grain-legume porridges (most commonly corn and soy), are frequently used for food aid purposes. Sorghum and cowpea have been suggested as alternative FBF commodities because they are drought-tolerant, grown locally in food aid receiving countries, and are not genetically modified. The objective of this thesis was to determine the protein quality and iron bioavailability of newly formulated, extruded FBFs in broiler chickens, which have been suggested as a good model for assessing iron bioavailability. Five FBFs were formulated to contain whey or soy protein to compare protein quality, sugar, oil, and an improved micronutrient premix. These included three white sorghum-cowpea FBFs; two were extruded with either whey protein concentrate (WSC) or soy protein isolate (WSC+SPI) added, one was non-extruded (N-WSC). Two others were white sorghum-soy (WSS) and corn-soy (CSB14) FBFs. Two additional white-sorghum cowpea FBFs were reformulated and “over-processed” to contain no sugar, less whey (O-WSC) or soy protein (O-WSC+SPI), and less oil, thus producing a less expensive FBF. Two studies were performed using prepared (Prep) or dry (Dry) FBFs, along with the United States Agency for International Development (USAID) corn and soy blend FBF, CSB+, fed to chickens for 3 and 2 weeks, respectively; food intake, body weights, hemoglobin, and hepatic iron were assessed. In the Prep study, new FBFs significantly increased caloric and protein efficiency compared to CSB+, despite similar food intake and body weight gain. In the Dry study, CSB+ significantly decreased food intake and caloric efficiency, with the exception of O-WSC+SPI, and nonsignificantly reduced body weight gain and protein efficiency compared to new FBFs. CSB+ significantly reduced hepatic iron content compared to all FBFs in the Dry study, and was nonsignificantly decreased compared to new FBFs in the Prep study. In conclusion, sorghum and cowpea FBFs performed similarly to corn and soy FBFs, suggesting these commodities are suitable replacements for corn and soy. Soy protein isolate (WSC+SPI) was an effective alternative to whey protein concentrate (WSC), suggesting SPI can be a less expensive protein supplement in FBFs. Surprisingly, non-extruded sorghum and cowpea (N-WSC) was equally efficacious to extruded WSC. However, N-WSC did not meet viscosity requirements and is not precooked, which limits its viability as an FBF. O-WSC+SPI resulted in poorer outcomes compared to other FBFs, which suggests the protein quality of cowpea may be inferior and the inclusion of whey protein is needed in this formulation, as O-WSC with whey performed similarly to other FBFs. Overall, new FBFs, with the exception of O-WSC+SPI, resulted in improved food efficiency and hepatic iron outcomes compared to CSB+, suggesting they are of higher nutritional quality. However, further research is needed to refine and identify the best FBF formulations.
Keywords: Fortified blended foods; Protein quality; Iron bioavailability; Broiler chicken model; Food aid; Sorghum